Sixth World Congress on Seafood Safety, Quality and Trade: 14-16 September 2005, Sydney, Australia - World Congress on Seafood Safety, Quality and Trade 2005 Sydney,Australia); James, D.; Ababouch, Lahsen; Washington, Sally; Food and Agriculture Organization of the United Nations (Rome: Food and Agriculture Organization of the United Nations, 2007)
Fish and fish products are among the most traded food commodities:close to 40 percent by volume ends up in international markets. Yet around three-quarters of fish exports finish up in just three markets: the European Union, Japan and the United States of America. China is an increasingly important player both as an exporter and an importer. Consumers expect that the fish they have access to will be safe and of acceptable quality, regardless of where they are produced or ultimately consumed. This has given rise to issues regarding fish quality and safety, international trade, risk analysis and harmonization of standards. These and other issues are addressed in this document.--Publisher's description.
World trade in seafood : key trends and issues -- Major importers:requirements and opportunities -- Building capacity for safety and quality New partnerships for achieving fish safety and quality.
Includes bibliographical references.
1
Keywords: Fishery processing .; Quality control -- Congresses; Fishery products -- Congresses